Using the desirability function as an effective tool in target costing model - Al Hazza, Muataz Hazza Faizi; Mohamed, Konneh; Iqbal, Mohammad; Taha, Assem Hatem; Muhammad, Hasibul Hasan (Trans Tech Publications, Switzerland, 2015)
High speed turning (HST) is an advanced machining process that uses higher cutting speeds than those used in conventional machining. HST enables manufacturers to shorten machining times. Therefore, this approach should be followed and justified by economic study. One of the most effective tools for economic study is by developing a target-cost model to control the machining cost. The aim of this research is to develop a target costing model for high speed turning. To achieve the aim of this research, a set of experimental data was obtained in the following cutting levels: cutting speed (500-700 m/min), feed rate (1000-2000 mm/min), and depth of cut of (0.1-0.3) mm. The materials used in this research were AISI 304 stainless steel as a work piece material and coated carbide as a cutting tool. The output data was used to develop a target costing model. The desirability function has been used to optimize the model